2005
DOI: 10.1029/2005gl023424
|View full text |Cite
|
Sign up to set email alerts
|

European spring and autumn temperature variability and change of extremes over the last half millennium

Abstract: We evaluate variability, trends, uncertainties, and change of extremes of reconstructed and observed European spring and autumn temperature back to 1500. Spring and autumn temperature experienced systematic century‐scale cooling compared to present conditions. The coldest springs appeared during the Maunder Minimum (ΔT = −1 K wrt 1901–2000). The amplitude of spring temperature variations at decadal and multidecadal scales doubles that of autumn and is most expressed in northeastern Europe. The decade 1995–2004… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
344
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 292 publications
(382 citation statements)
references
References 28 publications
28
344
1
Order By: Relevance
“…One purported advantage is the inclusion of longrange correlation structures, leading to predictive skill even at locations where no data is available for the past (Smerdon et al, 2011). Thus, even while these studies did not use predictors from Ireland, validation measures in these studies do indeed indicate skill for our area of interest (Luterbacher et al, 2004;Xoplaki et al, 2005;Pauling et al, 2006). Recently, it has been shown that even without explicitly including teleconnection patterns, reconstructions can still be skilful outside the area with good data coverage in the past (Werner et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One purported advantage is the inclusion of longrange correlation structures, leading to predictive skill even at locations where no data is available for the past (Smerdon et al, 2011). Thus, even while these studies did not use predictors from Ireland, validation measures in these studies do indeed indicate skill for our area of interest (Luterbacher et al, 2004;Xoplaki et al, 2005;Pauling et al, 2006). Recently, it has been shown that even without explicitly including teleconnection patterns, reconstructions can still be skilful outside the area with good data coverage in the past (Werner et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…During the winter of 1739-1740 Europe experienced very low temperatures. In Central and Eastern Europe the temperatures were 3-4 • C lower than in the reference period of 1961-1990(Luterbacher et al, 2004Xoplaki et al, 2005). Most parts of Southern Europe and the whole northwest also experienced lower temperatures ( Fig.…”
Section: The General Character Of the Crisismentioning
confidence: 99%
See 3 more Smart Citations